THE IMPLEMENTATION OF COLLABORATIVE LEARNING MODELS IN THE TEACHING METHOD SUBJECT FOR ENGLISH LITERATURE STUDENTS OF UMN AL-WASHLIYAH MEDAN - Vera Kristiana (Fakultas Sastra UMN AL Washliyah, 2021)
This research examined the application of the collaborative learning model in the eaching method subject for English literature students of UMN-AW Medan. The teaching method subject was one of the subjects that were considered confusing for English literature students of UMN-AW Medan. Students found it difficult to remember and understand every topic of discussion given in the lecture. This was due to the fact that there were so many materials presented in the teaching method lecture, namely about the types of English teaching methods both classical and modern. Students needed an appropriate learning model. The learning model was a collaborative learning model. The objective of the research was to foster the attitude and ability to work together in groups to achieve learning goals. Collaborative learning models could build knowledge through dialogue, share information with fellow students and lecturers so that students could increase self-confidence in the lecture process. Student self-confidence was needed in teaching method lectures considering that students were expected to be able to practice teaching with various methods that had been taught.